Unapologetic theology a Christian voice in a pluralistic conversion - Placher, William Carl, 1948- (Louisville, Kentucky Westminster, 1989)
Includes bibliographical references and index.
Keywords: Apologetics -- 20th century; Theology -- methodology; Philosophy, modern -- 20th century; Witchcraft; Liberalism; Relativism